information and communication technologies and their impact on changed the financial reporting system In a Sample in Iraqi banks - عبدالله, سلمان حسين; جاسم, رؤى احمد (Journal of Economics and Administrative Sciences, 2017)
paid recent developments in the information and communications technology and the accompanying developments in the global market to pay particular accounting information users to demand more sophistication in terms of corporate financial reporting systems, which led to the emergence of a new type of reporting (financial reporting in real time). where is the information and communications technology mainstay Nations for the development and progress, thanks to the development of technology that have made the transmission of information easily conducted and high speed to all who need it, communication is instantaneous and the flow of information via the internet dramatically exceeded the border temporal and spatial anywhere in the world, which resulted in the evolution of the accounting work in terms of systems and software used in business units advanced level of technology.